TATA KELOLA PEMERINTAHAN DIGITAL DALAM OPTIMALISASI PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) DI PROVINSI JAWA BARAT - Dani Mardian; Muh Ilham; Udaya Madjid; Andi Pitono (Jurnal Agregasi, 2026)
West Java Province is a pioneer in implementing digital payment for Motor Vehicle Tax (PKB). However, the optimization of PKB revenue continues to face challenges due to the suboptimal governance of digital government, as indicated by the low utilization of digital payment channels, which remains below 9%, and a declining trend in taxpayer compliance over the past five years. This study aims to analyze digital government governance in enhancing PKB revenue, identify inhibiting and enabling factors, and formulate an ideal governance model based on the OECD framework. This research employs a qualitative approach through observations, interviews, and document analysis, involving informants from government institutions, academia, and the public. The findings reveal that digital government governance has been implemented relatively well but has not yet had a significant impact on increasing PKB revenue. Inhibiting factors include system fragmentation, suboptimal use of data, and low levels of digital literacy, while enabling factors consist of institutional commitment, basic digital infrastructure, and service innovation. This study contributes a novel conceptual model, namely the SMART PKB Governance Framework, which is grounded in five core principles: Systematic, Measurable, Agile, Responsive, and Trusted